Identification of Water Carrying Capacity in Korpri Jaya Village, Sukarame Sub-District, Bandar Lampung City - Sobri, Achmad; Aprildahani, Baiq Rindang; Rasyid, Fachri Muhammad (Journal of Community Based Environmental Engineering and Management, 2026)
Water is a natural resource that has a vital role and function to fulfill the basic needs of all living things, especially humans, which need to be maintained. Korpri Jaya Village, Sukarame Sub-District, Bandar Lampung City is an area affected by the development of higher education institutions, namely UIN Raden Intan and the Sumatra Institute of Technology, which is characterized by a growing population and housing needs. There is a potential imbalance between water demand and water availability. Water demand is increasing due to population growth, while water availability is decreasing due to changes in land use and a lack of green open spaces. Even Bandar Lampung City has been identified as being in a state of water deficit based on the Strategic Environmental Assessment (KLHS). Therefore, it is necessary to identify the carrying capacity of water in Korpri Jaya Village. The analysis methods used in this study include a grid system approach and calculations of the environmental service index (IJLH) for water providers, which refer to surface water discharge to determine water carrying capacity. The results showed that Korpri Jaya Village has a water carrying capacity of 465,467 m³/year. Water carrying capacity is used as a reference point in spatial planning to anticipate potential water deficits in the future, along with increasing population and land use changes.